MECHANOSYNTHESIS OF MMC Cu-C DOPED WITH Ti FOR APPLICATION OF PANTOGRAPH CONTACT STRIP (PCS) - Andhika Abdan Rahmanullah; Pawawoi Pawawoi; Djoko Hadi Prajitno (BRIN, 2020)
This research was conducted to determine the effect of the addition of Titanium (Ti) and the sintering temperature variation on MMC CuC alloys as reinforcing elements. The process of this research uses powder metallurgical method with an alloying technique in Mechanical Alloying using a Planetary Ball Mill (PBM) machine with a speed of 600 rpm for 2 hours, the ratio of powder to the ball mill is 10:1. The compacting process is carried out using dies 11 mm in diameter and compacting pressure of 90 Kg/cm2. The sintering process is carried out three times, with variations in sintering of 800oC, 900oC, and 1000oC with sintering time for 1 hour in the tube furnace in the argon gas vacuum environment. The number of samples used in this study amounted to 9 samples with variations in alloy and temperature sintering, consist of MMC CuC alloy with addition of Ti 0%, 0.5%, 1.5% (T=800 oC), MMC CuC with addition of Ti 0%, 0.5%, 1.5% (T=900 oC), and MMC CuC with addition of Ti 0%, 0.5%, 1.5% (T=1000 oC). The tests included Vickers hardness testing, metallography testing, XRD testing, and SEM-EDS testing. The addition of Ti elements and varying sintering temperature had an effect on the hardness value of MMC CuC material with the highest hardness value in samples with 1.5% Ti alloy (800oC) which is 87.25 HV, and the lowest porosity value is 2.491% in the sample of 1.5% Ti (1000oC). Keywords : MMC CuC; Mechanical Alloying; Titanium; Pantograph Contact Strip